The correlation between students' anxiety and speaking achievement - Kamal, Moh. Zainol; Hodairiyah, Hodairiyah; Wardi, Moh. (Journal of Education and Learning (EduLearn), 2025)
The purpose of this study is to measure communicative apprehension, fear of negative evaluation, and test anxiety as predictors of students' anxiety with speaking achievement. The second goal was to determine the relative importance of the three predictors in predicting speaking achievement in Department of Islamic Education, Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni Sumenep. The samples of this research were 30 from 64 second-semester students in the 2022-2023 academic year. The data analysis using multiple regression were done by using SPSS. It found that the correlation between communicative apprehension and speaking achievement was -0.333, fear of negative evaluation and speaking achievement was -0.379, and anxiety of test and speaking achievement was -0.128. It means the three indicators of Anxiety were correlated with speaking achievement. Furthermore, the result of the T-test correlation of fear of negative evaluation with speaking achievement could be inferred that the T-test significant 0.0050.05, anxiety of test with speaking achievement was T-test significant 0.780.05. The conclusion, fear of negative evaluation is the best predictor of speaking achievement. Fear of negative evaluation provides a negative contribution. The higher the fear of negative evaluation students have, the lower achievement they have.